Emerging Pattern of Wind Change over the Eurasian Marginal Seas Revealed by Three Decades of Satellite Ocean-Surface Wind Observations - Lisan Yu (Remote Sensing, 2021)
This study provides the first full characterization of decadal changes of surface winds over 10 marginal seas along the Eurasian continent using satellite wind observations. During the three decades (1988–2018), surface warming has occurred in all seas at a rate more pronounced in the South European marginal seas (0.4–0.6 °C per decade) than in the monsoon-influenced North Indian and East Asian marginal seas (0.1–0.2 °C per decade). However, surface winds have not strengthened everywhere. On a basin average, winds have increased over the marginal seas in the subtropical/mid-latitudes, with the rate of increase ranging from 11 to 24 cms−1 per decade. These upward trends reflect primarily the accelerated changes in the 1990s and have largely flattened since 2000. Winds have slightly weakened or remained little changed over the marginal seas in the tropical monsoonal region. Winds over the Red Sea and the Persian Gulf underwent an abrupt shift in the late 1990s that resulted in an elevation of local wind speeds. The varying relationships between wind and SST changes suggest that different marginal seas have responded differently to environmental warming and further studies are needed to gain an improved understanding of climate change on a regional scale.